An Iterative Method for Solving the Problem of Pipeline Transportation of Gas along a Relief Track - Bazarov, Orifjon (E-Library Karshi EEI, 2021)
An Iterative Method for Solving the Problem of Pipeline Transportation of Gas along a Relief Track